(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Current time of globalization demands technology education integration for development of humanity by offering education at every door step in inclusive and efficient manner using different alternatives. The present article “Techno-Educo integration in current scenario” explores role of technological development to be used in education for better learning outcomes especially after covid-19 where digital technology has been proved to recover gap between learners and teachers in very smart, intelligent, efficient and attractive way offering multiple dimensions in teaching and learning. Technology has revolutionized teaching methods making teaching easy, smart, fun loving, fearless, repeatable, child centered, cost effective and promised for quality education. Digital classroom is offering better leaning outcome, engagement, collaboration, flexible education and utilization of latest digital resources without any gender biasing depicting barrier less education to all at global level. Educational apps represent technological involvement in education in terms of software making it easier and more affordable to all. Govt. of INDIA has also developed multiple apps and portals for promoting inclusive and quality education to all with help of information and communication technology (ICT). Media has also enlarged its space using technology and offered multiple places like blogs, digital story and multiple social media platforms for leaning, management, sharing of ideas, views, creativity and other digital information without any constraints. Various application of Techno-Educo integration is also discussed like convenient and innovative teaching learning, blended teaching, distance and e-leaning, teaching for CWSN, flexible and inclusive leaning style and many others exploring its importance according to current demands. The dark side of technology is also enlightened keeping in mind importance for safe and secure utilization of technology.